Pengaruh Store Atmosphere Dan Kualitas Layanan Terhadap Loyalitas Pelanggan (Studi Kasus Pada Pelanggan Cafe Sendi Malang) - Nurul Ahmadi; Khalikussabir Khalikussabir; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to determine how much influence the store atmosphere and quality of service to customer loyality. The sample in this study was taken as much 75 respondents and the technique used Accidental Sampling. The data in this study using a survey method through a questionnaire filled out by consumers. The results of this study can be concluded that store atmosphere and service quality have a significant effect on customer loyality either partially or simultaneously. Keywords: Store Atmosphere, Service Quality, Customer Loyality